Incidence of local complications and risk factors associated with peripheral intravenous catheter in neonates - Mitzy Tannia Reichembach Danski; Priscila Mingorance; Derdried Athanasio Johann; Stela Adami Vayego; Jolline Lind (SciELO, 2016)
Abstract OBJECTIVE To evaluate the incidence of complications related to the use of peripheral intravenous catheter in neonates and identify the associated risk factors. METHOD Prospective cohort study conducted in a Neonatal Intensive Care Unit. Participants were the hospitalized neonates undergoing peripheral intravenous puncture in the period from February to June 2013. RESULTS The incidence of complications was 63.15%, being infiltration/extravasation (69.89%), phlebitis (17.84%) and obstruction (12.27%). The risk factors were the presence of infection (p = 0.0192) and weight at the puncture day (p = 0.0093), type of intermittent infusion associated with continuous infusion (p <0.0001), endotracheal intubation (p = 0.0008), infusion of basic plan (p = 0.0027), total parenteral nutrition (P = 0.0002), blood transfusion associated with other infusions (p = 0.0003) and other drugs (p = 0.0004). Higher risk of developing complications in the first 48 hours after puncture. CONCLUSION A high rate of complications related to the use of peripheral intravenous catheter, and risk factors associated with infection, weight, drugs and infused solutions, and type of infusion.